P636 Real-world clinical effectiveness and safety of vedolizumab and ustekinumab in biologic-naïve patients with Crohn's disease: Results from the EVOLVE Expansion study. (30th January 2023) - Ferrante, M; Christensen, B; Bressler, B; Brett, N; Bassel, M; Kamble, P; Adsul, S; Gianchetti, L; Scharl, M
Abstract: Background: This study evaluated real-world clinical effectiveness and safety of vedolizumab (VDZ), a gut-selective α4β7-integrin inhibitor and ustekinumab (UST), an IL-12/23 p40 inhibitor, as first-line biologic treatment (Tx) for patients (pts) with Crohn's disease (CD). Methods: The EVOLVE Expansion study (NCT05056441) was a multicenter, observational, retrospective cohort study in biologic-naïve pts with CD (≥18 years old) who initiated VDZ or UST Tx in Australia, Belgium or Switzerland from 2016 to 2021. Data were collected from Tx initiation to initiation of chart abstraction, death or loss to follow-up, whichever came first. The time to event analysis was conducted using the Kaplan-Meier method and cumulative rates of clinical response, remission, mucosal healing and Tx persistence were estimated over 12, 24 and 36 months. Serious adverse events (SAEs), serious infections (SIs), CD exacerbations and CD-related surgeries were also evaluated. Inverse probability of treatment weighing was used to balance demographic and clinical characteristics across treatment groups. Results: 623 biologic-naïve pts with CD (VDZ 347, UST 276) from 31 sites were included. Baseline characteristics are presented in Table 1. Cumulative rates over 36 months were similar between VDZ- and UST-treated pts for clinical response (VDZ 82.0%, UST 84.1%; p=0.87) and clinical remission (VDZ 88.3%, UST 88.5%; p=0.67) (Table 2). Mucosal healing rates were significantly higher in VDZ- versus UST-treated pts (VDZ 91.3%, UST 87.4%, p=0.02), and treatment persistence was higher in UST-treated pts over 36 months (VDZ 70.6%, UST 80.3%; p=0.03). In VDZ cohort, 54 SAEs (including SIs) and 12 SIs occurred in 35/347 (10.1%) and 9/347 (2.6%) pts, respectively, while in UST cohort, 53 SAEs (including SIs) and 5 SIs occurred in 27/276 (9.8%) and 2/276 (0.7%) pts, respectively. There were no significant differences in the risk of CD exacerbations (HR 1.01; 95% CI, 0.68-1.49; p=0.98) and CD-related surgeries (HR 1.80; 95% CI, 0.69-4.73; p=0.23) between VDZ- and UST-treated pts. Conclusion: In real-world setting, clinical response and clinical remission were similar between VDZ and UST in biologic-naïve pts with CD. However, over 36 months mucosal healing was higher in the VDZ-treated pts, and Tx persistence was higher in UST-treated pts.